หลักการออกแบบการสอนบนเว็บตามแบบจำลอง ADDIE เพื่อการสอนสนทนาภาษาไทยเบื้องต้นสำหรับชาวต่างประเทศ (A WEB-BASED INSTRUCTIONAL DESIGN PRINCIPLE BASED ON ADDIE MODEL TO TEACH FUNDAMENTAL THAI CONVERSATION FOR FOREIGNERS) - วิบูลยศริน, วัชรพล (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2015)
การเรียนภาษาต่างประเทศควรให้ความสำคัญกับการพัฒนาทักษะการฟัง การพูด การอ่าน และการเขียนตามลำดับ โดยเน้นการฟังและการปฏิบัติตามคำสั่งได้ ฟังและตอบคำถามได้ หรือเล่าเรื่องจากการฟัง และแสดงความคิดเห็นได้ การสอนภาษาไทยในฐานะภาษาต่างประเทศจึงควรให้ความสำคัญกับการพัฒนาทักษะการฟังและการพูด หรือการสนทนาที่ผู้สอนและผู้เรียนจำเป็นต้องมีเวลามากเพียงพอในการฝึกฝนให้สามารถออกเสียงได้ใกล้เคียงกับเจ้าของภาษาให้มากที่สุดเป็นอันดับแรก เนื่องจากสภาพสังคมปัจจุบันที่เวลาเป็นสิ่งมีค่าและสำคัญ ผู้สอนหรือผู้เรียนอาจไม่มีเวลาเพียงพอหรือเวลาของผู้สอนและผู้เรียนไม่ตรงกันที่จะสามารถเรียนรู้และฝึกฝนได้มากนัก การนำเทคโนโลยีคอมพิวเตอร์เข้ามาจึงช่วยลดข้อจำกัดในการเรียนการสอนด้านนี้ลง โดยนำการสอนบนเว็บมาใช้เพื่อช่วยเสริมทักษะการสนทนาภาษาไทยเบื้องต้น โดยเน้นผู้เรียนเป็นศูนย์กลาง ซึ่งสามารถเรียนรู้ได้ทุกเวลา ทุกสถานที่ อย่างไรก็ตาม การออกแบบการสอนบนเว็บที่มีประสิทธิภาพควรดำเนินการตามแบบจำลอง ADDIE ซึ่งเป็นแบบจำลองที่ได้รับการยอมรับในการออกแบบการเรียนการสอนจากนักศึกษาส่วนใหญ่ ดังนั้น ในบทความนี้จึงมุ่งสังเคราะห์แนวคิดและนำเสนอหลักการออกแบบการสอนบนเว็บตามแบบจำลอง ADDIE เพื่อการสอนสนทนาภาษาไทยเบื้องต้นสำหรับชาวต่างประเทศให้เกิดประสิทธิภาพสูงสุด ตรงตามวัตถุประสงค์ของการเรียนการสอน และตอบสนองความต้องการของผู้เรียนแต่ละคน การสอนบนเว็บที่ได้จากการออกแบบตามแบบจำลองนี้จะสามารถนำไปใช้เป็นสื่อการเรียนการสอนเพื่อเสริมทักษะการสนทนาภาษาไทยของผู้เรียนให้มีประสิทธิภาพมากยิ่งขึ้น หรือเพื่อเตรียมความพร้อมและพัฒนาทักษะการสนทนาภาษาไทยเรื่องอื่นๆ มาล่วงหน้าก่อนเข้าชั้นเรียน คำสำคัญ: การออกแบบการสอนบนเว็บ แบบจำลอง ADDIE การสนทนาภาษาไทยเบื้องต้น ชาวต่างประเทศ Learning foreign language should focus on developing listening, speaking, reading, and writing skills respectively, emphasizing on listening and following instructions, listen and answer the questions, or narrating stories from listening and expressing their views. Hence, teaching Thai as a foreign language should firstly pay attention to develop listening and speaking skills or conversation that teachers and learners need to have enough time for practicing to be able to produce sound closed to a native-speaker as possible. In addition, social conditions at present, the time is value and important. Teachers or learners may not have enough time or the time between teachers and learners do not match that will learn and practice a lot. Computer technology plays a major role to reduce restrictions on this kind of instruction. Especially Web-based instruction, which brings about the application of information technology so learners can enhance fundamental Thai conversation skill as learner-centered that learning is anytime, anywhere. The optimal Web-based instruction, however, must encourage an instructional design oriented an ADDIE model which has been accepted as an instructional design from many educators. In this article is to synthesis ideas and present principles of a web-based instructional design to teach fundamental Thai conversation for foreigners in order to be maximum efficiency and meeting the instructional objectives and each student’s needs. Web-based instruction based on this model will be implemented as an instructional media for foreigners improving their conversation skill to be more effective or to prepare and develop other communicative skills before attending to the class. Keywords: Web-based Instructional Design, ADDIE Model, Fundamental Thai Conversation, Foreigners